THE IMPACT OF RELIABILITY AND CONTINUITY OF OPERATIONS ON CRISIS MANAGEMENT INFORMATION SYSTEMS - KLOCEK Faustyna; KORZENIEWSKI Michał (2018)
In today’s world, the IT systems have a huge influence on the functioning of public administration. IT systems become indispensable when managing processes and providing public services. There are very exposed to cyber attacks from other countries. It is said that there may be about 1000 attacks around the world every hour. This make difficult or impossible to work that systems, which ensure efficient functioning of the state. Crisis management system is particularly important for our security. That system allow to prevent threats and mitigating the consequences of disasters. Its integral part is reliable IT systems that are part of critical infrastructure. Therefore, we strive to ensure the continuity of the system, because only with the continuity of operations we are able to successfully and effectively operate in a crisis situation. An element of efficient public administration is reliable IT systems for crisis management. After a crisis situation, a huge amount of information is stored and processed. To facilitate the management of information, are created new tools that would be support decision making. One of them is Integrated Management Information Systems, thanks to which it is possible to prevent crises on a national scale. They work with virtual network technologies with the support of artificial intelligence.